MANAJEMEN PRODUKSI PESAN PROGRAM INOVASI KETILANG TUBERKULOSIS (TB) PUSKESMAS PURWOKERTO UTARA II - Nurcandrani, Prita Suci (LPPM-PMP Universitas Tidar, 2024)
Purwokerto Utara II Community Health Center, through the TB Ketilang Innovation Program determined the achievement of TB suspect service indicators of 100% or 297 people in 2023. However, in 2022, the number of findings only reached 79.79% of cases even though suspects had received information about the dangers of TB, healthy behavior (hygiene) and good sanitation. Meant, the expected change in behavior was not in accordance with the target. This research is to examine more deeply the application of message production management theory for the Tuberculosis Ketilang Innovation Program to TB suspects using Message Production Theory. This qualitative research used purposive sampling technique to draw the samples. The results showed that the Ketilang TB Innovation Program was successful in providing message interventions to increase awareness of the dangers of TB, especially in terms of the importance of maintaining sanitation and hygiene. In its implementation, involvement of TB cadres or survivors must be addressed.